PENGARUH KOMUNIKASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT KURNIA BUMI RAYA JAKARTA - Awalliya, Ayunita; Sabil, Sabil (Politeknik Negeri Lhokseumawe, 2025)
Abstract: This study examines the Influence of Communication and Work Discipline on Employee Performance at PT. Kurnia Bumi Raya Jakarta. Effective communication and high Work Discipline are two crucial factors in optimizing human resources, which in turn will improve the overall performance of the organization. Optimal Employee Performance is the main foundation for the success and sustainability of a company. The research method used is multiple linear regression, with statistical calculations based on the SPSS 26 application program. This data was collected through an online questionnaire using Google Form which was distributed to 55 employee respondents at PT. Kurnia Bumi Raya. The submission of questions in the questionnaire is presented in the form of written statements with answer choices. The results of hypothesis testing, both in the T test (Partial) and the F test (Simultaneous) show that Communication (X1) and Work Discipline (X2) have a significant influence on Employee Performance (Y). The significance value for the three variables is 0.000 0.05. Specifically, the t-count value for Communication (X1) is 2.808 and the t table is 2.006. and for that Work Discipline (X2) is 3.512 and t table 2.006. Meanwhile the f count value for simultaneous influence (Y) is 77.784 and f table 3.018. This finding indicates that both partially and simultaneously, Communication and Work Discipline contribute significantly to improving Employee Performance at PT. Kurnia Bumi Raya JakartaKeywords: Influence of Communication, Work Discipline, Employee Performance.